Astragaloside IV Attenuates Chronic Prostatitis by Activating Keap1/Nrf2/HO-1 Pathway: Suppressing Ferroptosis and Enhancing Antioxidant Defense - Shi J; Xuan Y; Zhang Q; Chen J; Zhu W; Zhang H; Duan Y (Journal of Inflammation Research, 2025)
Jintao Shi,1,* Yang Xuan,1– 3,* Qinyu Zhang,1,* Jiangtao Chen,1 Weihan Zhu,1 Hao Zhang,2,3 Yue Duan2,3 1The Second Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 2Department of Urology and Andrology, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of China; 3Zhejiang Provincial Key Laboratory of Sexual Function of Integrated Traditional Chinese and Western Medicine, Hangzhou, Zhejiang, 310005, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yue Duan; Hao Zhang, The Second Affiliated Hospital of Zhejiang Chinese Medical University, Xinhua Hospital of Zhejiang Province, No. 318, Chaowang Road, Hangzhou City, Zhejiang Province, People’s Republic of China, Email dyurology@163.com; htjtcm@163.comBackground: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS), a chronic inflammatory disorder with complex etiology and limited treatment options, is closely associated with oxidative stress and regulates cell death. Ferroptosis—an iron-dependent cell death driven by lipid peroxidation—amplifies CP/CPPS inflammation by concurrently triggering mitochondrial apoptosis and NLRP3 inflammasome activation, while Keap1/Nrf2/HO-1 axis serves as a central regulator bridging ferroptotic, apoptotic, and inflammatory cell death pathways. Astragaloside IV (AS-IV), a primary bioactive component of Astragalus membranaceus with established clinical use in urological therapies and favorable pharmacokinetics, was prioritized over structural analogs due to its unique dual-phase modulation: enhancing Nrf2 nuclear translocation without suppressing NF-κB-mediated immune surveillance. However, regulatory mechanisms linking AS-IV to ferroptosis inhibition in CP/CPPS remain unknown.Patients and Methods: This study aimed to investigate the therapeutic potential of astragaloside IV (the primary bioactive component of Astragalus membranaceus) for the treatment of CP/CPPS by suppressing ferroptosis via the Keap1/Nrf2/HO-1 pathway. A rat CP/CPPS model was established using complete Freund’s adjuvant (CFA), with animals divided into normal control, EAP, and AS-IV high/medium/low-dose groups and treated daily for four weeks. Additionally, a human prostatic epithelial cell (RWPE-1) inflammation model was induced by lipopolysaccharide (LPS), and cells were categorized into control, LPS, AS-IV medium-dose, ferroptosis inhibitor, and Nrf2 inhibitor + AS-IV medium-dose groups.Results: AS-IV ameliorated prostatic tissue inflammation and fibrosis, reduced lipid peroxidation marker malondialdehyde (MDA) levels, and enhanced antioxidant indicators, including glutathione (GSH) content and glutathione peroxidase 4 (GPX4) activity. Western blotting and immunohistochemical analyses further confirmed that AS-IV activated the antioxidant pathway by suppressing Keap1 expression, promoting Nrf2 nuclear translocation, and upregulating heme oxygenase-1 (HO-1) protein levels. Concurrently, pro-inflammatory cytokine levels, including tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6), were markedly reduced.Conclusion: This is the first study to demonstrate that AS-IV alleviates type III CP pathological damage by inhibiting ferroptosis via the Keap1/Nrf2/HO-1 axis, thereby providing experimental evidence for the development of multi-target therapeutic strategies based on natural products.Keywords: prostatic inflammation, lipid peroxidation, Nrf2, cellular redox balance, oxidative stress, pharmacological activation